Menopausal symptoms. Issue 7275 (16th December 2000) - Rymer, Janice; Morris, Edward P
Background: Definition: Menopause begins one year after the last menstrual period. Symptoms often begin in the perimenopausal years. Incidence/prevalence: In the United Kingdom the mean age for the menopause is 50 years 9 months. The median onset of the perimenopause is between 45.5 and 47.5 years. One Scottish survey (of 6096 women aged 45 to 54 years) found that 84% had experienced at least one of the classic menopausal symptoms, with 45% finding one or more symptoms a problem.1 Aetiology/risk factors: Urogenital symptoms of menopause are caused by decreased oestrogen concentrations, but the cause of vasomotor symptoms and psychological effects is complex and remains unclear. Prognosis: Menopause is a physiological event. Its timing may be genetically determined. Although endocrine changes are permanent, menopausal symptoms such as hot flushes, which are experienced by about 70% of women, usually resolve with time.2 However, some symptoms, such as genital atrophy, may remain the same or worsen. Aims: To reduce or prevent menopausal symptoms, and to improve quality of life with minimum adverse effects. Outcomes: Frequency and severity of vasomotor, urogenital, and psychological symptoms; quality of life. Methods: Clinical Evidence search and appraisal December 1999. We included only randomised controlled trials (RCTs) and systematic reviews that met Clinical Evidence quality criteria.